Question a:
f(6) = (6)² + 2(6) + 8
f(6) = 36 + 12 + 8
f(6) = 56
Question b:
f(x+4) = (x+4)² + 2(x+4) + 8
f(x+4) = x² + 8x + 16 + 2x + 8 + 8
f(x+4) = x² + 10x + 32
Question c:
f(-x) = (-x)² + 2(-x) + 8
f(-x) = x - 2x + 8
Answer:
The value of x for equation is 3.4
The value of y for equation is 5.2
Step-by-step explanation:
Given as :
The two linear equation are
2 x + y = 12 ........A
4 x - 3 y = 2 .........B
Now, Solving both equations , we get
3 × ( 2 x + y ) + (4 x - 3 y) = 3 × 12 - 2
Or, 6 x + 3 y + 4 x - 3 y = 36 - 2
Or, (6 x + 4 x) + (3 y - 3 y) = 34
Or, 10 x + 0 = 34
∴ x = ![\dfrac{34}{10}](https://tex.z-dn.net/?f=%5Cdfrac%7B34%7D%7B10%7D)
i.e x = 3.4
So, The value of x for equation , x = 3.4
Put the value of x into eq A
∵ 2 x + y = 12
Or, y = 12 - 2 x
Or, y = 12 - 2 × 3.4
Or, y = 12 - 6.8
∴ y = 5.2
So, The value of y for equation , y = 5.2
Hence, The value of x for equation is 3.4 and The value of y for equation is 5.2 Answer
Answer:
![\frac{512}{6561}](https://tex.z-dn.net/?f=%5Cfrac%7B512%7D%7B6561%7D)
Step-by-step explanation:
1) if according to the condition a₁=3 and r=2/3, then a₁₀ can be calculated as:
a₁₀=a₁*r⁹;
2) according to the rule above:
a₁₀=3*(2/3)⁹=512*3/(6561*3)=512/6561.
Answer:
is a trinomial having three terms, with degree 5 and the constant term '3'.
Step-by-step explanation:
Considering the trinomial
![4x^5\:+\:9x^2\:+\:3](https://tex.z-dn.net/?f=4x%5E5%5C%3A%2B%5C%3A9x%5E2%5C%3A%2B%5C%3A3)
As the polynomial contains 3 terms, so it is a trinomial.
As the highest power of the variable 'x' is 5, so the degree of this polynomial is 5.
Any term with no variable is called a constant term. so, 3 is a term with no variable. Therefore, the constant term is 3.
Therefore,
is a trinomial having three terms, with degree 5 and the constant term '3'.
Answer:
C. 4928 in2
Step-by-step explanation:
88 X 56 = 4928 in2